The Effect of Innovation, Economic Freedom, Macroeconomic Variables on GDP - Elina, Sefria; Setyadharma, Andryan (Efficient: Indonesian Journal of Development Economics, 2022)
The G-20 is a group of 19 countries with the largest economies in the world plus the European Union. Basically, the role of the G-20 in the economy is to maintain stable and high economic growth, realizing balanced growth between developed and developing countries. but based on data, the average GDP growth of the G-20 group in 2014 to 2019 was always below the world average even though the G-20 member countries had a systemic impact on the global economy. This study aims to analyze the effect of innovation, economic freedom, and macroeconomic variables on economic growth in the G-20. The data used in this research is secondary data. This study uses a fixed-effect model with panel data regression, consisting of 19 G-20 member countries for the 2009-2019 period. The results of this study indicate that innovation and economic freedom have no significant effect on economic growth in the 19 G-20 member countries. Inflation and population have a negative and significant effect on economic growth in the 19 member countries of the G-20. Meanwhile, FDI and trade have a positive and significant impact on economic growth in the 19 G-20 member countries. G-20 adalah 19 negara dengan ekonomi besar di dunia ditambah dengan organisasi Uni Eropa yang berperan untuk menjaga pertumbuhan ekonomi yang stabil dan tinggi antara negara maju dan negara berkembang. Berdasarkan data, rata-rata pertumbuhan PDB kelompok G-20 pada tahun 2014 hingga 2019 selalu berada di bawah rata-rata dunia meskipun negara-negara anggota G-20 berdampak sistemik terhadap perekonomian global. Penelitian ini bertujuan untuk menganalisis pengaruh inovasi, kebebasan ekonomi, dan variabel makroekonomi terhadap pertumbuhan ekonomi di G-20. Data yang digunakan adalah data sekunder. Penelitian ini menggunakan model fixed effect dengan regresi data panel, terdiri dari 19 negara anggota G-20 periode 2009-2019. Hasil penelitian ini menunjukkan bahwa inovasi dan kebebasan ekonomi tidak berpengaruh signifikan terhadap pertumbuhan ekonomi di 19 negara anggota G-20. Inflasi dan jumlah penduduk berpengaruh negatif dan signifikan terhadap pertumbuhan ekonomi di 19 negara anggota G-20. Sedangkan FDI dan perdagangan berpengaruh positif dan signifikan terhadap pertumbuhan ekonomi di 19 negara anggota G-20.